2018
DOI: 10.1039/c7cc08211h
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap-tunable black phosphorus quantum dots: visible-light-active photocatalysts

Abstract: Bandgap-tunable black phosphorus quantum dots prepared by a liquid exfoliation method in a mixture solvent of N-methylpyrrolidone and oleic acid can act as efficient photocatalysts for the degradation of rhodamine B. This is the first report on solely black phosphorus capable of destroying organic pollutants under visible light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…The peak of the UV–vis spectrum shown in Figure 2f indicates that the BP QDs have a thickness of one to two layers. The broad region at 450 nm is consistent with the previous result of BP QDs 40. Fourier‐transform infrared (FT‐IR) spectrum and identification of organic groups and chemical bonds are shown in Figure S6 in the Supporting Information.…”
Section: Resultssupporting
confidence: 89%
“…The peak of the UV–vis spectrum shown in Figure 2f indicates that the BP QDs have a thickness of one to two layers. The broad region at 450 nm is consistent with the previous result of BP QDs 40. Fourier‐transform infrared (FT‐IR) spectrum and identification of organic groups and chemical bonds are shown in Figure S6 in the Supporting Information.…”
Section: Resultssupporting
confidence: 89%
“…[2][3][4][5][6][7][8][9][10][11] Owing to the unique optical and electrical properties, BP holds large promise in the fields of energy and catalysis. [12][13][14][15][16][17][18][19] In particular, BP has a thicknessdependent direct bandgap ranging from 0.3 to 2.1 eV, leading to broad absorption spanning the ultraviolet (UV) and near-infrared only 25 min. The photocatalytic efficiency is comparable to that of previously reported BP/CN heterostructures composed of BP nanosheets or quantum dots.…”
Section: Visible-light Photocatalysismentioning
confidence: 99%
“…[33][34][35][36] Nevertheless, efficient synthesis of BP/CN heterostructures is still challenging and the BP materials used in production are typically limited to ultrathin nanosheets and quantum dots. [12][13][14][15][16][17][18][19] In particular, BP has a thicknessdependent direct bandgap ranging from 0.3 to 2.1 eV, leading to broad absorption spanning the ultraviolet (UV) and near-infrared All in all, an economical synthetic technique to prepare BPbased heterostructured photocatalysts is still lacking.…”
mentioning
confidence: 99%
“…According to the UV/Vis absorption curves and Kubeka‐Munk plots, the absorption of AgCl QDs is 391 nm with a band gap of 3.07 eV (Figure B). Compared to bulk AgCl, AgCl QDs have showed a significant blue shifted absorbance edges and extended band gaps (Figure A), which could be accredited to quantum confinement effect . Besides, it was found that visible light absorption edge of rGO/AgCl QDs has red shifted as compared with pristine AgCl QDs, indicating a narrowed band gap of AgCl QDs, which is attributed to the interfacial interaction between AgCl QDs and rGO .…”
Section: Resultsmentioning
confidence: 95%
“…Compared to bulk AgCl, AgCl QDs have showed a significant blue shifted absorbance edges and extended band gaps ( Figure S1A), which could be accredited to quantum confinement effect. 34,35 Besides, it was found that visible light absorption edge of rGO/AgCl QDs has red shifted as compared with pristine AgCl QDs, indicating a narrowed band gap of AgCl QDs, which is attributed to the interfacial interaction between AgCl QDs and rGO. 36 To further evaluate the interfacial contact between AgCl QDs and rGO, photoelectrochemical measurements were carried out.…”
Section: Resultsmentioning
confidence: 99%